Mechanical and fracture study of hybrid natural fiber reinforced composite – Coir and sugarcane leaf sheath. (2020) - Arul, M.; Sasikumar, K.S.K.; Sambathkumar, M.; Gukendran, R.; Saravanan, N.
Abstract: The mechanical properties polyester matrix composites reinforced with coir/SLS fibres were assessed in this paper. The mechanical properties like, tensile strength, flexural strength and impact strength were calculated. The fracture toughness of the composites are also studied. These fibres were employed into matrix resin in different weight percentage (25/75, 50/50, and 75/25) keeping total fiber weight percentage of 30% constant by using simple hand lay-up technique. The test were carried out in accordance with ASTM standards. The evaluation of the results display that the mechanical properties are higher in the 50/50 (Coir/SLS) hybrid composite than other combinations. There are signs that by the integration of both fibers in the polyester resin matrix will improve mechanical properties than pure polyester resin.